Characterization of natural killer and T cells in bronchoalveolar lavage and peripheral blood of sarcoidosis patients - Bergantini, Laura; d’Alessandro, Miriana; Del Zotto, Genny; Marcenaro, Emanuela; Bargagli, Elena (Frontiers in Immunology, 2023)
The characterization of frequency and phenotypes of natural killer (NK) cells and T cells in BAL and peripheral blood of patients with sarcoidosis was evaluated, to discriminate the differential status of these cells in these two compartments. The analysis revealed that CD56brightCD16neg resulted higher in BAL than PB of sarcoidosis and healthy subjects, while CD56dimCD16+ showed a different proportion between BAL and PB of both Sarcoidosis patients and HC. Moreover, in comparison with autologous PB, BAL was characterized by a higher expression of activated NK cell markers NKp44, CD69 and CD25. Significantly increased levels of PD-1+ NK cells in the BAL of patients were detected. Regarding the maturation of CD4 and CD8, an increase of Effector Memory T cells (TEM) was reported in BAL compared to PB. A better characterization of NK and T cells may lead to an improvement of the pathogenetic mechanisms in sarcoidosis.